Asuhan Keperawatan Pada Ny. R Dengan Preoperatif Dan Postoperatif Fraktur Femur Sinistra Di Ruang Rawat Inap Malibo Rsud Padang Pariaman - Kurnia Permata Sari; Linda Marni; Aulia Asman; Kheniva Diah Anggita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Femoral fracture is an emergency condition that can cause acute pain, impaired physical mobility, sleep pattern disturbances, and risk of infection. The main problem in patients with femoral fracture is the disruption of basic needs fulfillment due to physical limitations and pain responses that affect the healing process. This scientific paper aims to describe the comprehensive implementation of nursing care for patients with femoral fracture in order to improve the quality of nursing services and accelerate patient recovery. The method used was a descriptive case study with a nursing process approach, including assessment, nursing diagnosis, intervention planning, implementation, and evaluation. The research subject was Mrs. R with a medical diagnosis of left femoral fracture who was treated in the Malibo Inpatient Ward at RSUD Padang Pariaman. Data were collected through interviews, direct observation, physical examination, medical documentation, and relevant literature studies. The analysis results showed that the main nursing problems identified were acute pain, impaired physical mobility, sleep pattern disturbance, and risk of infection. Nursing implementation was carried out through pain management, mobility support, sleep support, and infection prevention. The case discussion showed that appropriate and continuous nursing interventions were able to reduce pain scale, improve mobility, enhance sleep patterns, and reduce the risk of infection.